Analysis of food insecurity and hunger on nigeria’s poverty level (Journal of Economic Research & Business Administration, 2023)
Food insecurity is lack of access to an adequate supply of affordable and wholesome food for a population. As a results of years of food decline, the number of individuals who experience poverty and consequently hunger have begun to rise on continual basis This study focuses on the food insecurity, hunger and poverty in Nigeria. The indicator of poverty is poverty rate while the indicators of food insecurity and hunger were food production index, prevalence of food inadequacy and number of the undernourished. The study employed autoregressive distributed lag (ARDL) model using time series data from 1990-2021. The study showed that food production index had negative impact on poverty level (p=.0008; t=-3.859645; coef. at -0.133758) and that undernourishment had significant negative impact on extreme poverty level (p=.0001; t=-4.861845). The study also found that the direction of causality between food production, hunger, and extreme poverty level showed that both food production and hunger granger caused extreme poverty (t=-4.152609, t=-2.250300 & t=5.317666 > t=2.0000).  The study suggested that in order to increase affordability, a distribution system for increased food production must be put in place to improve malnourishment